Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division Terhadap Kemampuan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 21 Padang - VERA MUSTIKA (Departemen Matematika, 2019)
Understanding of mathematical concepts is one of the purpose in mathematics learning. Understanding of mathematical concepts is the foundation for students to understand mathematics. But infact, Understanding of mathematical concepts of students at second grade SMPN 21 Padang waslow. It is caused by learning model that used has not facilitated students to develop their Understanding of mathematical concepts.One effort to overcome this problem is by applying Student Team Achievement Division of Cooperative Learning in mathematics learnings.This learning model helps students to develop their Understanding of mathematical concepts. The type of research is a quasi-experimental design with Static Group Design. The research hypothesis is carried out by using the t-test. These results indicate that the ability of students’ understanding mathematical concepts in learning that apply the model STAD is better than the ability of students’ understanding mathematical concepts in learning that apply direct learning. Keywords – Understanding of mathematical concepts, Student Team Achievement Division, Direct Learning